The Role of The Kebumen Government (Dinas Kumkm) in Digital Marketing Transformation in Marketing Kebumen MSME Products - Arifin, Sukron; Munawaroh, Siti; Winarsih, Eli; Achyar, M. Munir (Proceedings Series on Social Sciences & Humanities, 2025)
Digital marketing transformation has become a crucial aspect in the development of Micro, Small, and Medium Enterprises (MSMEs) in Kebumen Regency, especially in facing marketing challenges in the digital era. This study aims to analyze the role of the Department of KUMKM Kebumen in supporting the digital marketing transformation process among MSME actors. The research method employed is a qualitative approach with a case study design, encompassing interviews, observations, and policy document analysis. The findings reveal that the Kebumen KUMKM Service has implemented various programs that facilitate digitalization, such as training on the use of digital platforms and the introduction of effective online marketing techniques. However, challenges such as limited access to technology and low digital literacy remain significant barriers for MSME actors in optimally implementing digital marketing strategies. The study also finds that government policies have positively impacted the marketing of MSME products, leading to increased consumer trust and expanded market reach. To accelerate the adoption of digital marketing, further efforts are needed to enhance technological infrastructure and collaborate with broader digital platforms. This research is expected to contribute to the development of better policies in supporting the digital transformation of MSMEs in Kebumen.